The synergistic effect of Angelica sinensis (Oliv.) Diels and Rehmannia glutinosa (Gaertn.) DC. on antioxidant activity and protective ability against cell injury. Issue 8 (8th May 2022) - Zhang, Qingying; Yang, Tianzhi; Li, Dongmei; Ma, Mengyu; Liang, Xiaoling; Ma, Zixing; Ye, Qianglong; Yang, Hantao; Li, Minghui; Qu, Ailan; Chen, Yao
Abstract: Oxidative stress‐induced dysfunction of nerve cells has been implicated as a crucial cause of cell death in neurodegenerative diseases. In Asian countries, herbs, such as Angelica sinensis (Oliv.) Diels (DG) and Rehmannia glutinosa (Gaertn.) DC . (SDH), have long be considered to have antiaging abilities. The herbs act as neuro protectants that rescue nerve cells from oxidative stress damage and apoptosis. Thus, developing herbal formulas can potentially lead to new treatments for neurodegenerative diseases. In this study, we compared the effective active components and antioxidant properties of extractive of DG and SDH (DG‐SDH) when formulated at different ratios. DG‐SDH formulated at a ratio of 3:2 (DG‐SDH [3:2]) produced the highest content of polysaccharides, polyphenols, and flavonoids. It also showed the best ability in removing DPPH and hydroxyl free radicals compared to single herb or other compounding ratio. The antioxidant activity of DG‐SDH (3:2) showed best synergistic effects in scavenging activity assays of DPPH free radicals and hydroxyl free radicals. DG‐SDH (3:2) could increase the cell viability of SHSY‐5Y cells, PC‐12 cells, and BV‐2 cells. In particular, DG‐SDH (3:2) protected SHSY‐5Y cells from H2 O2 ‐induced cell injury by inhibiting excessive expression of reactive oxygen species (ROS), reducing the rate of apoptosis and restoring mitochondrial membrane potential. Actin‐Tracker Green and DAPI staining and fluorescence microscope observation confirmed that DG‐SDH (3:2) helped in preserving cell morphology under oxidative stress. These findings support that DG‐SDH (3:2) promote the neuroprotection against hydrogen peroxide and can serve as a novel therapy for neurodegenerative diseases. Practical applications: This is the first study to investigate DG and SDH interaction between effective ingredients. These findings support that DG‐SDH (3:2) has the best synergistic effects in antioxidant activity and promote the neuroprotection against hydrogen peroxide. Hence, DG‐SDH (3:2) will be an excellent candidate to be developed as a functional food ingredients or nutraceuticals for neurodegenerative diseases. Abstract : Angelica sinensis ( Oliv .) Diels (DG) and Rehmannia glutinosa ( Gaertn. ) DC. (SDH) can act as neuro protectants. DG‐SDH formulated at a ratio of 3:2 (DG‐SDH (3:2)) increased content of polysaccharides, polyphenols, and flavonoids and showed the best synergistic effects in scavenging activity of free radicals. DG‐SDH (3:2) protected SHSY‐5Y cells by scavenging reactive oxygen species (ROS), reducing cell apoptosis, increasing mitochondrial membrane potential and protecting cell morphology.